2014
DOI: 10.3389/fpls.2014.00746
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and biochemical constraints imposed by salt stress: learning from halophytes

Abstract: Soil salinization is one of the most important factors impacting plant productivity. About 3.6 billion of the world’s 5.2 billion ha of agricultural dry land, have already suffered erosion, degradation, and salinization. Halophytes are typically considered as plants able to complete their life cycle in environments where the salt concentration is above 200 mM NaCl. Salinity adjustment is a complex phenomenon but essential mechanism to overcome salt stress, with both biophysical and biochemical implications. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Maintenance of shoot and root vigor is dependent mainly on photosynthetic capacity (Duarte et al, 2014;Penella et al, 2015). Photosynthetic activity remained unchanged in A/A25 plants under salt conditions compared to their controls and, therefore, also in the supply of photosynthates to plants, as confirmed by the absence of reduced plant growth.…”
Section: Discussionmentioning
confidence: 80%
“…Maintenance of shoot and root vigor is dependent mainly on photosynthetic capacity (Duarte et al, 2014;Penella et al, 2015). Photosynthetic activity remained unchanged in A/A25 plants under salt conditions compared to their controls and, therefore, also in the supply of photosynthates to plants, as confirmed by the absence of reduced plant growth.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, T. gallica have an ability to dissipate excessive energy. This is one of the most common mechanisms by which halophytes overcome the accumulation of excessive reducing power, the primary source of ROS, avoiding this way the photo-destruction of the photosynthetic apparatus [54]. Gusman et al [49] showed the decrease in the quantum yield of photosynthetic electron transport and the electron transport rate followed by the increase in the non-photochemical quenching in lettuce plants treated with As, indicating that the most part of excitation energy was dissipated as non-photochemical process, probably as part of an internal protection mechanism of the photosynthetic apparatus, as suggested by Konrad et al [55].…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…Additionally, ongoing climate change (increasing drought frequency and intensity, increased air temperature and salt water intrusion in coastal soils) must also be taken into account, as must the consequences (Duarte et al . ). Salt stress in glycophytes is associated with a reduction in leaf expansion, stomatal closure, reduced primary production, biomass losses and nutritional deficiencies, e.g .…”
Section: Introductionmentioning
confidence: 97%